Paternal high‐fat diet enhances offspring whole‐body insulin sensitivity and skeletal muscle insulin signaling early in life. Issue 5 (27th February 2018) - Consitt, Leslie A.; Saxena, Gunjan; Slyvka, Yuriy; Clark, Brian C.; Friedlander, Max; Zhang, Yizhu; Nowak, Felicia V.
Abstract: Evidence suggests that paternal diet can predispose offspring to metabolic dysfunction. Despite this knowledge, little is known regarding the effects of paternal high‐fat feeding on offspring insulin sensitivity. The purpose of this study was to investigate for the first time the effects of paternal high‐fat feeding on whole‐body and skeletal muscle insulin action in young and adult offspring. At 4 weeks of age, founder C57BL6/N males (F0) were fed a high‐fat diet or control diet for 12 weeks and then bred with females on a control diet. Offspring (F1) were euthanized at 6 weeks, 6 months, or 12 months and insulin‐stimulated insulin signaling was measured ex vivo in isolated soleus muscle. At 6 weeks of age, paternal high fat offspring (HFO) had enhanced whole‐body insulin sensitivity (35%, P  <   0.05), as well as, increased insulin‐stimulated skeletal muscle phosphorylation of Akt threonine 308 (70%, P  <   0.05) and AS160 threonine 642 (80%, P  <   0.05) compared to paternal control fed offspring (CFO), despite both offspring groups consuming standard chow. At 6 months of age, HFO had increased percent body fat compared to CFO (74%, P  <   0.005) and whole‐body and skeletal muscle insulin signaling normalized to CFO. Body fat was inversely related with insulin signaling in HFO, but not CFO. These findings suggest that paternal high‐fat feeding contributes to enhanced whole‐body and skeletal muscle insulin sensitivity in HFO early in life; however, these benefits are lost by early adulthood, potentially due to premature increases in body fat. Abstract : Paternal high‐fat feeding induces early enhancements in skeletal muscle insulin signaling in offspring. Increases in body fat later in adulthood are associated with declines in skeletal muscle insulin signaling in these mice.